The incidence and prevalence of psychiatric illness in Ireland: a progress report - Walsh, Dermot (Statistical and Social Inquiry Society of Ireland, 1976)
Epidemiological observations deal broadly with the estimation of the incidence and prevalence of a given condition both in local communities, in whole nations as well as some sections of whole nations, such as the black and white races within the United States and internationally. For some conditions it is possible to set up a predictable standard prevalence and incidence of a condition, at least for a limited time period and it becomes possible then to search for variations from these standard incidences and prevalences. Where such deviations are discovered the next step is to seek environmental factors prevailing in this community which may be intuitively or experimentally suspected of influencing incidence and prevalence.
Read before the Society, 15 January 1976
Keywords: Psychiatric illness in Ireland; Incidence of psychiatric illness; Prevalence of psychiatric illness; Mental health; 314.15